Institutional support and teaching practices for students with intellectual disabilities in inclusive schools in Indonesia - Widajati, Wiwik; Budiati, Eryana Fatimasari Retno; Sartinah, Endang Pudjiastuti; Ludfi, Muhammad Kholid Ni’amul; Susena, Yuda Sakti (Edelweiss Applied Science and Technology, 2026)
Inclusive education has become an essential framework for ensuring equitable access to quality education for students with intellectual disabilities. Institutional support and effective teaching practices play a critical role in facilitating successful inclusive education implementation. This study aims to explore institutional support mechanisms and teaching practices for students with intellectual disabilities in inclusive schools in Surabaya, Indonesia. This research employed a qualitative approach using in-depth interviews, classroom observations, and document analysis involving classroom teachers, special education teachers, and school leaders from three inclusive schools. The findings indicate that institutional support is reflected in inclusive education policies, administrative commitment, individualized education planning, and collaborative support systems. Teaching practices include curriculum adaptation, differentiated instruction, visual learning strategies, and individualized assistance to support students’ cognitive and socio-emotional development. However, challenges remain in terms of limited teacher training, insufficient specialized resources, and workload constraints. Institutional commitment and collaboration among stakeholders significantly contribute to improving educational access and participation for students with intellectual disabilities. Strengthening teacher capacity, improving institutional support systems, and enhancing resource availability are essential to ensure sustainable, inclusive education practices. This study contributes to understanding inclusive education implementation in developing country contexts and provides practical implications for improving inclusive education quality.